PENINGKATAN NILAI-NILAI AGAMA DAN MORAL MELALUI METODE BERCERITA PADA ANAK USIA 4-5 TAHUN - Purba, Erna; Yusuf, Abas; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
This research is a form of action research with descriptive methods . Subjects were teachers and 1 child of 20 children . Based on the research that has been done and through the results obtained after the analysis of the data held that : 1 ) Planning learning to develop religious values ??and morals through storytelling in children can be categorized as